Potential for innate-like responsiveness of resident T cells in human skin: a new perspective on tissue immune-surveillance. (25th February 2016) - Woolf, Richard; Nussbaumer, Oliver; Hayday, Adrian
Abstract: Background: The skin contains many resident immune cells that are key for tissue homoeostasis. In mouse skin, a distinct population of T cells have the innate-like capacity to respond rapidly to markers of tissue stress, rather than requiring clonal, antigen-specific activation. This lymphoid stress surveillance response (LSSR) is key to host immunity, contributing to cancer immunosurveillance and cutaneous atopy. We sought to identify whether the potential for LSSR exists in human skin. Methods: We adapted a novel skin explant protocol to study the skin-resident lymphocyte compartments of over 100 healthy donors. Normal adult skin was obtained as discarded material after cutaneous surgery. Skin-resident lymphocytes were characterised by flow cytometry, and their functional potentials assessed in vitro with different models of activation. Ethics approval was granted by a local research ethics committee (REC 06/Q0704/18) Findings: We established that human skin contains a large reproducible population of γδ T cells, which were distinct from γδ T cells in the blood. These cells displayed features of tissue-resident memory T cell receptor (TCR) αβ+ cells, but strikingly had the capacity to become activated by ligands for the NKG2D receptor, independent of the TCR, which is analogous to innate-like T cells in mouse skin. Such responsiveness was not seen in other NKG2D+ T cells. Upon NKG2D-mediated activation, skin-resident γδ T cells showed robust T helper-1-like and cytotoxic effector responses, and in some donors interleukin 13 production. These cells also displayed profound cytolytic activity against transformed epithelial cells in vitro, in part mediated via NKG2D. Interpretation: To our knowledge, these data provide the first clear identification of human tissue-resident innate-like T cells, which strongly argues for the existence of LSSR in human tissues and places skin-resident γδ T cells in the early afferent phase of the immune response. This finding offers a new perspective on tissue immune surveillance, possibly representing a common feature of barrier tissues, and has implications for future studies in human skin immunobiology. Funding: Medical Research Council, Wellcome Trust, Cancer Research UK.